Economic Development in Asia - Dowling, J. Malcolm (Cengage Learning Asia, 2004)
ECONOMIC DEVELOPMENT IN ASIA explores factors that influence economic growth and development particularly from an asian development perspective. Grounded firmly on theoretical foundations, it showcases the richness and variety of the Asian development experience through extensive coverage of individual country case studies, institutional developments, and challenges facing policy-makers in the region as well as in-depth discussions of existing empirical evidence. This book is specially tailored to meet the needs of social science students studying economic development in Asia. University students, educators and government policy makers will find the book particularly useful for understanding growth and development trends in the context of a rapidly globalizing world. With the rising tide of interest in Asian economies, the book will prove to be an invaluable for anyone seeking to better understand the process of growth and economic development in the region